Mapa de zonificación geotécnico del proyecto de vivienda de interés social "09 de Junio" ubicado en el barrio Menfis Alto en el cantón y provincia de Loja - Ruiz Escovar, Henry Vicente (2024)
The purpose of this research was to carry out the "Geotechnical zoning map of the "09 de Junio" social housing project, located in the Menfis Alto neighborhood in Loja’s city". The work began with the topographic survey at 1: 2000 scale, which served as a basis for the geological survey where geo-materials such as sandstones, conglomerates, shales, and clays belonging to the Belén formation, together with sandstones with lenses of conglomerates and limonites belonging to the Trigal formation were found. For the geotechnical exploration, direct and indirect approaches such as Standard Penetration Tests (SPT) and vertical electrical soundings (VES) were applied. Regarding direct methods, a total of 7 SPT surveys up to 10 meters deep were analyzed. From the samples obtained, laboratory tests, such as granulometry, moisture content, Atterberg limits, AASTHO, and SUCS classification were carried out. According to ASTM standards, and with these results, the bearing capacity of the soils, liquidity index, relative consistency, and behavior of the clay layers were calculated. Among the indirect approaches, 6 SEV tests were analyzed, which allowed us to know the lithological distribution at depth and the characteristics of these layers concerning the humidity present in the area. With variables such as topography, lithology, structure, load capacity, and humidity, a geotechnical zoning map was drawn up at a scale of 1:2000. Based on the results of this research, some preventive measures such as the channeling of surface water, urban and non-urban zones are recommended. Key words: Topography, Geology, Geotechnical characterization, zoning.